2008
DOI: 10.1111/j.1365-3040.2008.01835.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep supercooling xylem parenchyma cells of katsura tree (Cercidiphyllum japonicum) contain flavonol glycosides exhibiting high anti‐ice nucleation activity

Abstract: Xylem parenchyma cells (XPCs) of boreal hardwood species adapt to sub-freezing temperatures by deep supercooling to maintain a liquid state of intracellular water near -40°C. Our previous study found that crude xylem extracts from such tree species exhibited anti-ice nucleation activity to promote supercooling of water. In the present study, thus, we attempted to identify the causative substances of supercooling. Crude xylem extracts from katsura tree (Cercidiphyllum japonicum), of which XPCs exhibited deep su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 78 publications
(125 reference statements)
6
57
0
Order By: Relevance
“…Based our results, Kasuga et al 2008 found that some flavonol glycosides isolated from the xylem parenchyma cells had a high level of SFC activity. Furthermore, the hydrolyzable tannins in deep supercooling xylem cells in Cercidiphyllum japonicum exhibited the SFC activity like flavonol glycosides Wang et al, 2012 .…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Based our results, Kasuga et al 2008 found that some flavonol glycosides isolated from the xylem parenchyma cells had a high level of SFC activity. Furthermore, the hydrolyzable tannins in deep supercooling xylem cells in Cercidiphyllum japonicum exhibited the SFC activity like flavonol glycosides Wang et al, 2012 .…”
Section: Discussionmentioning
confidence: 91%
“…Even if the concentration of all the active compounds having the SCF activity is increased, their activities become constant at a certain concentration FIG.2, Kawahara et al, 1996a;Kawahara et al, 2000;Kasuga et al, 2008 . It was thought that this was due to the fact that the surface area of the ice nucleus was fixed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations